GPTS DAN MASA DEPAN EKONOMI INDONESIA - I Putu Hedi Sasrawan; Gede Crisna Wijaya (Adisam Publisher, 2025)
This study explores the role of General Purpose Technologies (GPTs) as fundamental drivers of long-term economic transformation and analyzes the prospective impact of Artificial Intelligence (AI) on the future of the Indonesian economy. GPTs, characterized by their pervasiveness, continuous improvement, and ability to foster complementary innovations, historically trigger profound structural changes. However, their full productivity benefits are often delayed, a phenomenon known as the